Effect of triparanol on atherosclerosis and on sterol composition and concentration in serum and aorta of the chicken* - Harry Y.C. Wong; Joel Avigan; Robert L. Raiford; Ann Butler; Hugh E. Vroman (Journal of Lipid Research, 1963)
The administration of triparanol resulted in an increase in serum total sterols and desmosterol in both cockerels and egg-laying pullets. In cockerels treated for 20 weeks with 25.0 mg of triparanol/kg body weight, the total serum sterol level was 106 mg/100 ml compared to 80 mg/100 ml for the controls. Desmosterol represented 76% of these sterols in the triparanol-treated birds while none was detectable in the serum of the controls. In the aortas of these cockerels, desmosterol was not detectable in the controls but represented 67% of total sterols in those receiving triparanol. In egg-laying pullets, a similar but more pronounced effect was observed. Administration of 40.0 mg of triparanol/kg body weight for 10 weeks resulted in an increase of total serum sterols from 65 mg/100 ml to 522 mg/100 ml, of which 90% was desmosterol. Pullets treated for 2 weeks with 50–100 mg of triparanol/kg body weight showed about a fourfold increase in serum sterols, up to 83% of which was desmosterol. In all cases, the administration of triparanol caused a cessation of egg production. It appears that triparanol enhances the degree and incidence of atherosclerosis of the aorta of the chicken.